HIV Disease hospitalizations and factors associated with in‐hospital mortality in Ecuador: A nationwide analysis from 2015 to 2023 - German Josuet Lapo‐Talledo; Ángel Luis Zamora Cevallos; Carlos Rafael Arteaga Reyes; Sánchez Redrobán, José; Jhon Ernesto Delgado Pinargote; Ángela María Espinoza Guevara; Edgar Antonio Menéndez Cuadros (My University, 2025)
Human immunodeficiency virus (HIV) remains a significant public health concern worldwide, contributing to notable rates of hospitalization and mortality. This study aimed to analyse HIV disease hospitalization trends and factors associated with in‐hospital mortality in Ecuador during 2015–2023. Methods Official national hospital discharge data were used. Hospitalization and in‐hospital mortality rates were calculated. Multivariable logistic regression was performed to obtain adjusted odds ratios (aORs) and 95% confidence intervals (CIs) to identify factors associated with in‐hospital mortality. Results: Totally 28 408 HIV disease hospitalizations were analysed; the majority were males 61.19% (n = 17 383). Average hospitalization rate was 18.48 per 100 000 inhabitants. In‐hospital deaths accounted for 11.31% (n = 3214). Older age (≥40 years) was significantly associated with a higher likelihood of death, particularly in 60–69 years (aOR 1.78, 95% CI 1.49–2.13) and ≥70 years (aOR 1.79, 95% CI 1.36–2.34). Patients with HIV‐related Pneumocystis jirovecii pneumonia (aOR 2.74, 95% CI 2.28–3.29) and multiple malignant neoplasms (aOR 4.30, 95% CI 1.66–11.15) had the highest mortality likelihood. Although a declining trend in mortality rates was observed throughout 2015–2023, there was an increase in mortality probabilities in 2021 which may be linked to healthcare disruptions during the COVID‐19 pandemic, while subsequent decline in 2022 and 2023 suggests improvements in HIV care access.ConclusionsWhile HIV‐related hospitalizations and mortality have declined in Ecuador, older patients and those with severe opportunistic infections or malignancies remain at higher risk. These findings underscore the need for early diagnosis, enhanced management of HIV‐related complications and sustained antiretroviral therapy (ART) coverage, particularly during public health crises.